Association between meat, fish, and fatty acid intake and incidence of acute myeloid leukemia and myelodysplastic syndrome: the Japan Public Health Center-based Prospective Study - Yoshimitsu Shimomura; Tomotaka Sobue; Ling Zha; Tetsuhisa Kitamura; Motoki Iwasaki; Manami Inoue; Taiki Yamaji; Shoichiro Tsugane; Norie Sawada (Komiyama Printing Co. Ltd, 2023)
Background: The association between meat, fish, or fatty acid intake and acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS) has been investigated in a few studies, and the results were inconsistent. In addition, most studies are mainly based on the United States and European countries, in which the dietary patterns differ from that in Asia. Therefore, the risk of AML/MDS from meat, fish, or fatty acid intake in Asia requires further exploration. The aim of this study was to investigate the association between AML/MDS incidence and meat, fish, or fatty acid intake using the Japan Public Health Center-based prospective study. Methods: The present study included 93,366 participants who were eligible for analysis and followed up from the 5-year survey date until December 2012. We estimated the impact of their intake on AML/MDS incidence using a Cox proportional hazards model. Results: The study participants were followed up for 1,345,002 person-years. During the follow-up period, we identified 67 AML and 49 MDS cases. An increased intake of processed red meat was significantly associated with the incidence of AML/MDS, with a hazard ratio of 1.63 (95% confidence interval, 1.03-2.57) for the highest versus lowest tertile and a Ptrend of 0.04. Meanwhile, the intake of other foods and fatty acids was not associated with AML/MDS. Conclusion: In this Japanese population, processed red meat was associated with an increased incidence of AML/MDS.